Pengembangan Model Nasi Pecel Tiga Rasa dalam Pembelajaran Kimia pada Sekolah Menengah Atas - Budiarto, Itok Dwi (SCAD Independent, 2024)
This study aims to: (1) produce a model of Nasi Pecel 3 Rasa in high school chemistry learning; (2) determine the quality of the model of Nasi Pecel 3 Rasa in high school chemistry learning that has been developed. This study is a type of research and development (R&D) with the ADDIE development model design. The study was conducted at SMAN 2 Kediri. The research data sources include: (1) analysis sources, namely class XI MIPA students in the 2016/2017 academic year, literature, curriculum documents and materials; (2) expert validation sources, namely chemistry teachers of SMAN 2 Kediri, (3) class trial sources, namely 30 class XI MIPA 2 students (experimental class) and 26 class XI MIPA 9 students (control class) in the 2017/2018 academic year. Data were collected using questionnaires, observations, tests. The collected data were analyzed using qualitative descriptive analysis, quantitative descriptive analysis, and inferential analysis. The results of the research are: (1) the 3 Flavors Pecel Rice model in high school chemistry learning which includes syntax, social systems, reaction principles, support systems, instructional impacts and accompaniments; (2) the 3 Flavors Pecel Rice model in high school chemistry learning which is valid, practical and effective.